2019
DOI: 10.1111/jfpp.13935
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of meat by spinach on physicochemical and nutritional properties of chicken burgers

Abstract: This study describes the replacement of meat by spinach on physicochemical and nutritional properties of chicken burgers. Three batches of chicken burgers were manufactured: control (burgers prepared with 100% of chicken meat), E10 (burgers manufactured with 10% of spinach and 90% of chicken meat), and E30 (burgers prepared with 30% of spinach and 70% of chicken meat). The replacement of meat by spinach significantly affected the color parameters, decreasing L*, a*, and b* values with the increasing of spinach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
18
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 53 publications
6
18
0
2
Order By: Relevance
“…We observed lower (P < 0.05) lipid content for fresh turkey sausages prepared with 20% and 30% carrot (5.42 and 5.26 g/100 g, respectively) when compared with control sausages (7.53 g/100 g). This outcome agrees with the findings of Carvalho et al, 5 in which the incorporation of spinach reduced the amount of lipid in chicken burgers. The reduction in fat content is attributable to the low amount of fat incorporated in the vegetables (i.e., carrot) and the elimination of the added turkey fat, resulting in lower fat values.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…We observed lower (P < 0.05) lipid content for fresh turkey sausages prepared with 20% and 30% carrot (5.42 and 5.26 g/100 g, respectively) when compared with control sausages (7.53 g/100 g). This outcome agrees with the findings of Carvalho et al, 5 in which the incorporation of spinach reduced the amount of lipid in chicken burgers. The reduction in fat content is attributable to the low amount of fat incorporated in the vegetables (i.e., carrot) and the elimination of the added turkey fat, resulting in lower fat values.…”
Section: Resultssupporting
confidence: 93%
“…3,4 In this regard, the conversion of vegetables into ingredients, for their later incorporation in meat product formulations, could be a good strategy to enhance the quality and image of processed meat. 1,5 Carrot (Daucus carota L.) is a vegetable appreciated for its orange root. It is part of a group of foods widely used for their nutritional value, health benefits, and technological properties, 6 and it is a rich source of vitamin A (beta carotene) and dietary fiber.…”
Section: Introductionmentioning
confidence: 99%
“…According to the researchers, these results may be explained by the water-and fatholding capacity of the sugarcane fibre. The results obtained by Carvalho et al (2019) regarding the physicochemical proprieties of chicken burgers partially substituted with spinach, demonstrated that the substitution of the meat with spinach significantly affected the colour parameters, decreasing the values of L*, a* and b* as spinach addition was increased. Kehlet et al (2017) increased the aroma, texture and grainy flavour of meatballs by the addition of rye bran.…”
Section: Introductionmentioning
confidence: 98%
“…The results obtained by Carvalho et al . () regarding the physicochemical proprieties of chicken burgers partially substituted with spinach, demonstrated that the substitution of the meat with spinach significantly affected the colour parameters, decreasing the values of L *, a * and b * as spinach addition was increased. Kehlet et al .…”
Section: Introductionmentioning
confidence: 99%
“…Food trends have their origin in the new needs of consumers related to nutrition and concern for health ( Carvalho et al., 2019 ). Thus, consumers demand natural products, which limits the industry in their use of synthetic additives in foods ( Pateiro et al., 2018a , Lorenzo et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%